Evaluation of Host Defense Peptide (CaD23)-Antibiotic Interaction and Mechanism of Action: Insights From Experimental and Molecular Dynamics Simulations Studies - Ting, Darren Shu Jeng; Li, Jianguo; Verma, Chandra S.; Goh, Eunice T. L.; Nubile, Mario; Mastropasqua, Leonardo; Said, Dalia G.; Beuerman, Roger W.; Lakshminarayanan, Rajamani; Mohammed, Imran; Dua, Harminder S. (Frontiers in Pharmacology, 2021)
Background/aim: Host defense peptides (HDPs) have the potential to provide a novel solution to antimicrobial resistance (AMR) in view of their unique and broad-spectrum antimicrobial activities. We had recently developed a novel hybrid HDP based on LL-37 and human beta-defensin-2, named CaD23, which was shown to exhibit good in vivo antimicrobial efficacy against Staphylococcus aureus in a bacterial keratitis murine model. This study aimed to examine the potential CaD23-antibiotic synergism and the secondary structure and underlying mechanism of action of CaD23. Methods: Peptide-antibiotic interaction was evaluated against S. aureus, methicillin-resistant S. aureus (MRSA), and Pseudomonas aeruginosa using established checkerboard and time-kill assays. Fractional inhibitory concentration index (FICI) was calculated and interpreted as synergistic (FIC<0.5), additive (FIC between 0.5-1.0), indifferent (FIC between >1.0 and 4). SYTOX green uptake assay was performed to determine the membrane-permeabilising action of CaD23. Molecular dynamics (MD) simulations were performed to evaluate the interaction of CaD23 with bacterial and mammalian mimetic membranes. Circular dichroism (CD) spectroscopy was also performed to examine the secondary structures of CaD23. Results: CaD23-amikacin and CaD23-levofloxacin combination treatment exhibited a strong additive effect against S. aureus SH1000 (FICI=0.60-0.69) and MRSA43300 (FICI=0.56-0.60) but an indifferent effect against P. aeruginosa (FIC=1.03-1.15). CaD23 (at 25μg/ml; 2xMIC) completely killed S. aureus within 30 mins. When used at sub-MIC concentration (3.1μg/ml; 0.25xMIC), it was able to expedite the antimicrobial action of amikacin against S. aureus by 50%. The rapid antimicrobial action of CaD23 was attributed to the underlying membrane-permeabilising mechanism of action, evidenced by the SYTOX green uptake assay and MD simulations studies. MD simulations revealed that cationicity, alpha-helicity, amphiphilicity and hydrophobicity (related to the Trp residue at C-terminal) play important roles in the antimicrobial action of CaD23. The secondary structures of CaD23 observed in MD simulations were validated by CD spectroscopy. Conclusions: CaD23 is a novel alpha-helical, membrane-active synthetic HDP that can enhance and expedite the antimicrobial action of antibiotics against Gram-positive bacteria when used in combination. MD simulations serves as a powerful tool in revealing the peptide secondary structure, dissecting the mechanism of action, and guiding the design and optimisation of HDPs.